Production of kojic acid. - Ariff, Arbakariya; Mohamad, Rosfarizan; Prabu, Rajagopal; Kapri, Mohammad Rizal; Lajis, Ahmad Firdaus (2010)

(untitled)
The present invention discloses a method of producing kojic acid that includes cultivation of a fungal strain in the form of mycelia in a fermenter and biotransformation of sugars to kojic acid in a cell suspension system. The cell suspension system comprises the cultivated mycelia re-suspended in a solution containing a reaction buffer and sugar that includes hydrolysed starch, glucose and/or sucrose.